Identification of the Distribution of Seawater Intrusion Using the Resistivity 2D Method in the Belawan Area, North Sumatra Province - Said Muzambiq; Amir Husin; Netti Herlina; Tri Maylani Gultom (Jurnal Ilmu Lingkungan, 2025)
Excessive withdrawal of deep groundwater has an impact on changing the direction of groundwater flow so that the hydrostatic pressure decreases, resulting in seawater intrusion. This study aims to determine the areas indicated by seawater intrusion and determine the direction of distribution of saltwater contaminants. The method used is the Schlumberger configuration resistivity geoelectric method to obtain resistivity values with a path length of 200 meters. In the research results obtained in the field, processing using Ms. Excel and interpreted using IP2WIN.. The results of the processing using IP2WIN are then processed using Surfer to draw the correlation between Track I and Track III in 2D form. Line I which indicated seawater intrusion, namely the seventh layer with a resistivity value of 0.198 m, was designated as seawater intrusion. Track II shows seawater intrusion, namely in the sixth layer seawater intrusion is found with a resistivity value of 0.0584 m. Track III shows the presence of seawater intrusion, namely in the eighth layer seawater is found with a resistivity value of 0.0035 m. Based on the research conducted, the distribution of seawater intrusion from Track I on Jalan Raya Belawan, Belawan Harbor, Bagan Deli Village, Medan Belawan District, which is close to the beach. Seawater intrusion flows to the southwest which is the location of Track II and Track III through the groundwater layer affected by the intrusion.